Supervised injection facilities in Canada: past, present, and future - Thomas Kerr; Sanjana Mitra; Mary Clare Kennedy; Ryan McNeil (BMC, 2017)
Abstract Canada has long contended with harms arising from injection drug use. In response to epidemics of HIV infection and overdose in Vancouver in the mid-1990s, a range of actors advocated for the creation of supervised injection facilities (SIFs), and after several unsanctioned SIFs operated briefly and closed, Canada's first sanctioned SIF opened in 2003. However, while a large body of evidence highlights the successes of this SIF in reducing the health and social harms associated with injection drug use, extraordinary efforts were needed to preserve it, and continued activism by local people who inject drugs (PWID) and healthcare providers was needed to promote further innovation and address gaps in SIF service delivery. A growing acceptance of SIFs and increasing concern about overdose have since prompted a rapid escalation in efforts to establish SIFs in cities across Canada. While much progress has been made in that regard, there is a pressing need to create a more enabling environment for SIFs through amendment of federal legislation. Further innovation in SIF programming should also be encouraged through the creation of SIFs that accommodate assisted injecting, the inhalation of drugs. As well, peer-run, mobile, and hospital-based SIFs also constitute next steps needed to optimize the impact of this form of harm reduction intervention.